Study on the Trajectory Planning Method for High Bearing Capacity of Joint Manipulator - Tang Runzhi; Li Tiejuni; Yang Dongi (Jixie chuandong)
Aiming at the problem of low deadweight ratio of load in joint manipulator，two trajectory planning methods to improve the bearing capacity of the joint manipulator are proposed. The first method gets a new trajectory，this method automatically generates a set of moment smooth motion trajectories by using the correct dynamics model and selecting acceleration values of segmented motion process，the appearance of large peak torque will be avoided by this method. The second method optimizes the existing trajectory，this method first selects a standard predefined motion curve as trajectory. The torque peak of the manipulator is suppressed to lowest by using genetic algorithms to optimize the motion parameters of the curve. The appearance of large peak torque will also be avoided by this method. Through the simulation of Adams，it is found that the joint torque is optimized compared with other commonly used trajectory when lifting heavy objects in these ways. Finally，the correctness and effectiveness of the control method are verified through the experiment.